Transparency of Wakalah Bil Ujrah Contracts in Sharia Digital Banking Services: Analysis of Application Interfaces - Madi, Minhajuddin; Said, Muhammad; Ahmad, Ahmad; Sr, Naharuddin; Putra, Arya Nirwansyah Dwi (Jurnal Iqtisaduna, 2025)
This study aims to analyze the transparency of the wakalah bil ujrah contract in the user interfaces of Islamic digital banking applications in Indonesia. The research employs a descriptive qualitative method with content analysis, focusing on observing features that potentially use this contract, such as transfers and payments, in three dedicated Islamic banking apps: BSI Mobile, Muamalat DIN, and MyBCA Syariah. The findings reveal two main points: First, the level of transparency in explaining the contract type and its fee mechanism is notably low across all observed applications. Second, the application of the wakalah bil ujrah contract itself is not uniform; it was identified in BSI Mobile and Muamalat DIN, but not found in the equivalent features of MyBCA Syariah. This indicates that the core issue is a systemic lack of transparency, regardless of the specific contract applied. This study recommends enhancing transparency through improved UI/UX design that explicitly presents contract information, integrating embedded Sharia literacy features, and developing stricter regulatory technical guidelines for standardized Sharia contract communication in digital platforms.